Solve for x:
Answers
Answered by
1
Given,
a/(x-a) + b/(x-c) = 2c/(x-c)
To find the value of x ,
Solution :-
a/(x-a) + b/(x-c) = 2c/(x-c)
⇒ a/(x-a) + b/(x-c) = c/(x-c) + c/(x-c)
⇒ a/(x-a) - c/(x-c) = c/(x-c) - b/(x-c)
⇒ a(x-c) - c(x-a) / (x-a) (x-c) = (c-b)/(x-c)
(x-c) cancel out from each side , we get,
⇒ ax - ac - cx + ac / (x-a) = (c-b)
⇒ ax - cx / (x-a) = (c-b)
⇒ (a-c)x = (c-b) (x-a)
⇒ (a-c)x = (c-b)x - a(c-b)
⇒ (a-c)x - (c-b)x = -a(c-b)
⇒ (a-c-c+b)x = -a(c-b)
⇒ (a+b-2c)x = a(b-c)
⇒ x = a(b-c) / (a+b-2c)
Answered by
0
=>(a−c)x=(c−b)x−a(c−b)
= > (a - c)x - (c - b)x = - a(c - b)=>(a−c)x−(c−b)x=−a(c−b)
= > (a - c - c + b)x = - a(c - b)=>(a−c−c+b)x=−a(c−b)
Similar questions